The Influence of Buffet Food Quality and Experiential Marketing on Repurchase Intention Through Customer Satisfaction - Ahmad Alamsyah; Efendi Efendi; Al Agus Kristiadi (Jurnal Info Sains : Informatika dan Sains, 2026)
The study aims to analyze the effect of buffet food quality and experiential marketing on repurchase intention through customer satisfaction, Case Study of Cafe Gran Via Jakarta. The study uses quantitative research with a survey approach to obtain customer responses to the Case Study of Cafe Gran Via Jakarta. The sampling technique uses purposive sampling with the aim of obtaining customers who have enjoyed food at Cafe Gran Via Jakarta more than once. The distribution period of the research instrument from November 15, 2023 to December 31, 2023 obtained 250 respondents. The data analysis technique uses PLS-SEM. Results of the study: Buffet food quality and experiential marketing have a positive and significant effect on customer satisfaction and has a influence on repurchase intention. While customer satisfaction can be a mediator variable. Recommendation: to vary the buffet food menu periodically by adding new, attractive and innovative dishes so as to increase repurchase intention and create a friendly and pleasant environment for customers to strengthen relationships with existing customers and attract new customers to return to buy food at Cafe Gran Via Jakarta.